Potential Unemployment Insurance Duration and Labor Supply: The Individual and Market-Level Response to a Benefit Cut - Johnston, Andrew C.; Mas, Alexandre (Journal of Political Economy, 2018)
We examine how a 16-week cut in potential unemployment insurance (UI) duration in Missouri affected search behavior of UI recipients and the aggregate labor market. Using a regression discontinuity design (RDD), we estimate marginal effects of maximum duration on UI and nonemployment spells of 0.45 and 0.25, respectively. We simulate the unemployment rate implied by the RDD estimates assuming no market-level externalities. The implied response closely approximates the decline in the unemployment rate following the benefit cut, suggesting that, even in a period of high unemployment, the labor market absorbed the influx of workers without crowding out other job seekers.